Internalizing the character of discipline in integrated Islamic school students - Anita, Anita; Wuryandani, Wuri (ScienceRise: Pedagogical Education, 2019)
The aim of this study is to review theoretically the internalization of the character of discipline in SDIT (Sekolah Dasar Islam Terpadu/ Integrated Islamic Primary School) students. This theoretical study originated from high public interest in SDIT. This becomes an interesting thing. Some print media said that this interest was based on several reasons. One of them is planting characters. This character planting is in accordance with Presidential Regulation No. 87 Th 2017 concerning strengthening character education. At SDIT they have carried out character education for a long time. Character education is carried out in the process of internalization in the SDIT environment, which both internalize the characters in the school environment. The character that is highlighted is discipline. Internalization of the character of this discipline can be done through five stages that are collaborated with character discipline indicators. Based on the discussion of theoretical studies that have been presented it is concluded that the process of internalizing the character of discipline in integrated Islamic elementary school students and it is occurs through five stages of the disciplinary characters developed in SDIT students. Based on the discussion of theoretical studies that have been presented review theoretically: 1) The internalization of the character in students, it is concluded that the process of internalizing the character of discipline in integrated Islamic elementary school students; 2) The process of estlabishing discipline in SDIT students, it is occurs through five stages of the disciplinary characters developed in SDIT students